2004
DOI: 10.1002/ijc.20689
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of allelic imbalances at multiple cancer‐related chromosomal loci and microsatellite instability within the same tumor using a single tumor gland from colorectal carcinomas

Abstract: Genetic changes related to colorectal carcinomas are accumulated in individual tumor glands during disease progression. Microsatellite allelic analysis of individual tumor glands from 30 colorectal carcinomas using a polymerase chain reaction (PCR) assay coupled with crypt isolation was used to detect intratumoral genetic heterogeneity, the sequence of allelic imbalances (AIs) and the microsatellite instability status of single tumor glands during neoplastic progression. In addition, the CpG islands methylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 29 publications
1
24
2
Order By: Relevance
“…RNA was also obtained from normal stomach glands using the crypt isolation technique as described previously. (30) Gene expression analysis. Real-time PCR was carried out using TaqMan Gene Expression Assays (Applied Biosystems, Foster City, CA, USA) and a 7900HT Fast Real-Time PCR System (Applied Biosystems) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was also obtained from normal stomach glands using the crypt isolation technique as described previously. (30) Gene expression analysis. Real-time PCR was carried out using TaqMan Gene Expression Assays (Applied Biosystems, Foster City, CA, USA) and a 7900HT Fast Real-Time PCR System (Applied Biosystems) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It is believed that the adenoma-carcinoma sequence underlies the development of colorectal cancer in most patients, and two distinct pathways have been identified -the microsatellite instability (MSI) and the chromosomal instability (CIN) pathways 2 -6 . Discovery of these two pathways has led to the paradigm of colorectal cancer as a genetically heterogeneous disease 2,5,7 . Colorectal cancer with MSI has a better prognosis than stage-matched microsatellitestable cancer 8 -12 .…”
Section: Introductionmentioning
confidence: 99%
“…It has long been established that gastric cancers develop from a single gland cell that undergoes an accumulation of genetic changes (1), and which eventually results in a malignant tumor with monoclonal character (2,3). Recent molecular genetic evidence also supports this concept (1).…”
Section: Introductionmentioning
confidence: 97%
“…According to established theory, these accumulated genetic alterations can be identified by loss of heterozygosity (LOH) at many chromosomal loci within the tumor (4). It is also true that differences between tumor glands are thought to cause genetic heterogeneity within the same tumor (1)(2)(3), and some studies stated that genetic heterogeneity is frequently found in individual gastric cancers (5)(6)(7). Such genetic heterogeneity within the same tumor complicates the development of a tumor-treatment strategy based on tumor pathogenesis (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation